PENGARUH EARNING PER SHARE (EPS), DEVIDEND PER SHARE (DPS) DAN PRICE EARNING RATIO (PER) TERHADAP HARGA SAHAM PT. BANK RAKYAT INDONESIA, TBK PERIODE 2015-2019 - Muhammad Rifani; Muhammad Hasanur Arifin; Irwansyah Irwansyah (Smart Business Journal, 2021)
This study discusses the partial and simultaneous influence between Earning Per Share (EPS), Devidend Per Share (DPS) and Price Earning Ratio (PER) on Stock Prices in PT. Bank Rakyat Indonesia, Tbk for the 2015-2019 Period. This research is a quantitative method research with asosiatif kausal research type. Annual report of PT. Bank Rakyat Indonesia is the population on this research, The sample used was the PT. Bank Rakyat Indonesia, tbk financial statements 2015-2019 period with the sampling technique used was nonprobability sampling by purposive sampling. The type of data used in this study is secondary data that contains PT. Bank Rakyat Indonesia, tbk financial reports 2015-2019 period. The technique of collecting data by literature study and documentation. Data analysis techniques in this study used multiple regression analysis. The results of the study prove that Earning Per Share (EPS) is partially insignificant to the share price related to the significance level of 0,068 > 0,05 with an effective contribution value of -69.5%. Devidend Per Share (DPS) is partially has no significant effect on the share price related to the significance level of 0,163 > 0.05 with an effective contribution value of 9.8%.  and Price Earning Ratio (PER) is partially significant toward the share price related to the significance level of 0,046 ≤ 0.05 with an effective contribution value of 159.4%.  simultaneously Earning Per Share (EPS), Devidend Per Share (DPS) and Price Earning Ratio (PER) have insignificant effect on stock prices with a sig value of 0,068 > 0,05. Magnitude of influence of 99,7%.  Keyword: Earning Per Share (EPS), Devidend Per Share (DPS) and Price Earning Ratio (PER) and stock prices